Postnatal management of growth failure in children born small for gestational age - Adriane A. Cardoso‐Demartini; Margaret C.S. Boguszewski; Cresio A.D. Alves (Brazilian Society of Pediatrics, 2019)
Objectives: To discuss the etiology and growth consequences of small size at birth and the indications, effects, and safety of biosynthetic growth hormone therapy in children born small for gestational age. Source of data: A comprehensive and non‐systematic search was carried out in the PubMed, LILACS, and SciELO databases from 1980 to the present day, using the terms "small for gestational age," "intrauterine growth restriction," and "growth hormone". The publications were critically selected by the authors. Data synthesis: Although the majority of children born small for gestational age show spontaneous catch‐up growth during the first two years of life, some of them remain with short stature during childhood, with high risk of short stature in adult life. Treatment with growth hormone might be indicated, preferably after 2-4 years of age, in those small for gestational age children who remain short, without catch‐up growth. Treatment aims to increase growth velocity and to reach a normal height during childhood and an adult height within target height. Response to growth hormone treatment is variable, with better growth response during the pre‐pubertal period. Conclusions: Treatment with growth hormone in short children born small for gestational age is safe and effective to improve adult height. Efforts should be done to identify the etiology of small size at birth before treatment. Resumo: Objetivos: Discutir a etiologia e as consequências para o crescimento e as indicações, os efeitos e a segurança da terapia com hormônio de crescimento biossintético em crianças pequenas para idade gestacional. Fonte dos dados: Uma busca abrangente e não sistemática foi feita nas bases de dados PubMed, LILACS e SciELO de 1980 até a presente data, com os termos "small for gestational age" (pequeno para a idade gestacional), "intrauterine growth restriction" (restrição de crescimento intrauterino) e "growth hormone" (hormônio do crescimento). As publicações foram selecionadas criticamente pelos autores. Síntese dos dados: Embora a maioria das crianças nascidas pequenas para idade gestacional apresente recuperação espontânea do crescimento durante os dois primeiros anos de vida, algumas delas permanecem com baixa estatura durante a infância, com alto risco de baixa estatura na vida adulta. O tratamento com hormônio de crescimento pode ser indicado, preferencialmente após os dois aos quatro anos, naquelas crianças sem recuperação espontânea do crescimento e com baixa estatura. Seus objetivos são aumentar a velocidade de crescimento e atingir uma altura normal durante a infância e uma altura adulta dentro da altura‐alvo. A resposta ao tratamento com hormônio de crescimento é variável, com melhor resultado se iniciado durante o período pré‐puberal. Conclusões: O tratamento com hormônio de crescimento em crianças baixas nascidas pequenas para idade gestacional é seguro e eficaz para melhorar a estatura adulta. Esforços devem ser feitos para identificar a etiologia do nascimento pequenas para idade gestacional antes do tratamento. Keywords: Small for gestational age, Catch‐up, Growth hormone, Short stature, Adult height, Palavras‐chave: Pequeno para a idade gestacional, Catch‐up, Hormônio de crescimento, Baixa estatura, Estatura adulta